Dietary advanced glycation end-products and their associations with body weight on a Mediterranean diet and low-fat vegan diet: a randomized, cross-over trial - Kahleova, Hana; Znayenko-Miller, Tatiana; Motoa, Giulianna; Eng, Emma; Prevost, Alex; Uribarri, Jaime; Holubkov, Richard; Barnard, Neal D. (Frontiers in Nutrition, 2024)
Objective Evidence suggests that changes in dietary advanced glycation end-products (AGEs) may influence body weight, but the effects of different dietary patterns remain to be explored. The aim of this study was to compare the effects of a Mediterranean and a low-fat vegan diet on dietary AGEs and test their association with body weight. Materials and methods In this randomized cross-over trial, 62 overweight adults were assigned to a Mediterranean or a low-fat vegan diet for 16-week periods in random order, separated by a 4-week washout. Body weight was the primary outcome. Three-day diet records were analyzed using the Nutrition Data System for Research software and dietary AGEs were estimated, using an established database. Statistical approaches appropriate for crossover trials were implemented. Results Dietary AGEs decreased by 73%, that is, by 9,413 kilounits AGE/day (95% −10,869 to −7,957); p < 0.001, compared with no change on the Mediterranean diet (treatment effect −10,303 kilounits AGE/day [95% CI −13,090 to −7,516]; p < 0.001). The participants lost 6.0 kg on average on the vegan diet, compared with no change on the Mediterranean diet (treatment effect −6.0 kg [95% CI −7.5 to −4.5]; p < 0.001). Changes in dietary AGEs correlated with changes in body weight (r = +0.47; p < 0.001) and remained significant after adjustment for total energy intake (r = +0.39; p = 0.003). Conclusion Dietary AGEs did not change on the Mediterranean diet but decreased on a low-fat vegan diet, and this decrease was associated with changes in body weight, independent of energy intake. Clinical trial registration https://clinicaltrials.gov/, identifier NCT03698955